SPEAK UP Pedagogy Produces Highest Expressive and Analytical Speaking Scores in Students: Pedagogi SPEAK UP Menghasilkan Nilai Berbicara Ekspresif Dan Analitis Tertinggi Siswa Dasar - Mulkan Inra; Nazurty Nazurty; Ahmad Syarif (Academia Open, 2026)
General Background The development of fundamental communication competencies is a global priority to prepare students for twenty-first-century challenges. Specific Background In the Indonesian primary education context, conventional teacher-centered methods limit active oral practice, resulting in low student confidence, restricted vocabulary, and passive communication. Knowledge Gap Existing research predominantly evaluates project-oriented pedagogy in higher education or foreign language settings, leaving a critical deficit regarding its application to simultaneous expressive and analytical communication for young learners in semi-rural areas. Aims This study investigates the application of the SPEAK UP instructional framework and standard Project Based Learning on the expressive and analytical oral competencies of fifth-grade students at SD Negeri 282/VI Bangko. Results Utilizing a quantitative quasi-experimental design with 87 participants, statistical analysis via One Way ANOVA revealed significant variations among the pedagogical groups. The SPEAK UP framework generated the highest overall mean score of 87.33, outperforming both the standard project methodology at 82.14 and conventional instruction at 70.52. Specific to analytical oral communication, the experimental framework achieved a mean of 87.87. Novelty This research pioneers the integration of structured expressive practice and analytical knowledge construction within a project-based framework specifically tailored for young demographic cohorts in non-urban settings. Implications Educational practitioners can adopt this structured instructional framework to facilitate active, student-centered learning, fulfilling modern curriculum demands and resolving traditional communication barriers. Highlights The SPEAK UP framework generated an optimal overall mean score of 87.33. Standard project pedagogy successfully outperformed conventional instruction by achieving an 82.14 mean. Structured oral practice resolved traditional communication barriers among fifth-grade participants. Keywords Analytical Speaking; Expressive Speaking; Primary Education; Project Based Learning; SPEAK UP Model